The impacts of integrated STEM education on Students’ learning motivation - Van Thien Ngo (Technium Social Sciences Journal, 2021)
The purpose of this study was to determine the effect of STEM (Science, Technology, Engineering, Math) activities on learning motivation of the first-year students and the students’ view on STEM. A mixed research method was used. In the quantitative section of the study, the pre-test and post-test experimental single group design were used, whereas the qualitative research was conducted with the interview. The survey questionnaire and interview form were used as data collection instruments. Forty-first-year students attending at Cao thang Technical College participated in this study. A 6-week program was conducted with STEM education through an industrial project. The paired sample T-test was used to determine the significant difference between pre-test and post-test motivation scores of students participating in STEM activities. The students’ view on STEM education demonstrated that STEM improved their learning motivation. Furthermore, the students also consolidate students’ careers before entering the job market.